Model Pembelajaran SENTRIS (Student Engagment, Exploration, Nurturing Thinking, Transformation, Reflection Innovation, Synergy) Untuk Meningkatkan Partisipasi Peserta Didik Pada Pembelajaran Sains - Taufiq, A. Muhammad Haerul; Kadir, St. Fatima; Palennari, Muhiddin (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Science education plays a crucial role in developing students' scientific thinkingskills and critical, creative, and innovative character. However, science learning inschools is still dominated by conventional, teacher-centered approaches, resultingin low student participation and engagement. Several learning models, such asInquiry Learning, Problem-Based Learning, and Discovery Learning, have beenimplemented, but they have not been able to comprehensively integrate emotionalengagement, reflection, and social collaboration. To address this, the CENTRIS(Student Engagement, Exploration, Nurturing Thinking, Transformation, Reflection,Innovation, Synergy) Learning Model was developed, emphasizing seven stages ofcontinuous learning. This model is oriented towards student-centered learning,facilitating active student involvement, exploration, reflection, innovation, and socialsynergy in science learning. This article was written using a literature study methodthrough analysis of various journals, books, and related articles. The results of thestudy indicate that the CENTRIS model can increase students' active participation,creativity, and scientific understanding, making science learning more meaningful,reflective, and collaborative.